Profile of warfarin users served in a public pharmacy in a municipality in the interior of Bahia (Research, Society and Development, 2021)
Anticoagulants are substances that prevent the formation of clots in the blood, being widely used in cardiovascular problems. One of the most used oral anticoagulants in the last 50 years is Warfarin, which has been proven to be effective in preventing some diseases, such as acute myocardial infarction, venous thromboembolism, systemic embolism, atrial fibrillation, among others. Despite its effectiveness, this drug has a narrow therapeutic margin, where its therapeutic dose is very close to lethal, and thus, it can cause toxic effects to users. Thus, this study aims to describe the profile of warfarin users treated at the public pharmacy of a Basic Health Unit, in Vitória da Conquista (a municipality in the interior of Bahia). This is a quantitative and cross-sectional study with a descriptive design, carried out with 10 participants. Questionnaires were applied to warfarin users, the data collected will be analyzed, following all the ethical questions of the study. The results of this research reveal a profile of more men than women, where the reasons for the use of warfarin among them are very common, being 60% for stroke, 20% of the interviewed participants have used the drug for more than 12 months, and also use it. of other drugs simultaneously, which is a very important factor to be monitored so that no drug interactions occur and also reduce the risk of adverse reactions. It is concluded that the drug in question is of paramount importance for all who use it, and therefore, this study adds to the importance of monitoring the anticoagulant therapy, due to the risks it can generate for the patient, no result obtained was absolute or it can be considered 100% assertive, which is why more research related to the topic in larger populations and samples is needed, through more comprehensive data collection in basic health units in general, for future articles or work.